Recent exploits of the ISOLTRAP mass spectrometer - Kreim, Susanne; Atanasov, Dinko; Beck, Dietrich; Blaum, Klaus; Böhm, Christine; Borgmann, Christopher; Breitenfeldt, M.; Cocolios, T. E.; Fink, Daniel; George, Sebastian; Herlert, A.; Kellerbauer, Alban; et al. (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2013)
The Penning-trap mass spectrometer ISOLTRAP, located at the isotope-separator facility ISOLDE (CERN), is presented in its current form taking into account technical developments since 2007. Three areas of developments are presented. The reference ion sources have been modified to guarantee a sufficient supply of reference ions for mass measurements and systematic studies. Different excitation schemes have been investigated for manipulation of the ion motion in the Penning trap, to enhance either the purification or measurement process. A multi-reflection time-of-flight mass separator has been implemented and can now be routinely used for purification and as a versatile tool for beam analysis.
Gesehen am 27.10.2021